The effect of aridification on dry and wet habitats of Illancs microregion, SW Great Hungarian Plain, Hungary - Ladányi, Zsuzsanna; Deák, Áron; Rakonczai, János (Acta Geographica Debrecina Landscape & Environment series, 2010)
By the beginning of the 21st century, investigations aiming landscape history and landscape changes became especially important in the environmental research. The decreasing number of natural areas called the attention of the world to the rapid changes in the landscape caused by human activities and climate change. Certain places are facing with increased problems caused by the sensitiveness of landscapes. In Hungary, in the Danube–Tisza Interfluve a continuous groundwater-table sinking process was observed, as a result of anthropogenic effects of the last century and the consequences of climate change. On the highest part of this mesoregion (e. g. Illancs microregion), the decrease of the groundwater-level has reached 7 metres compared with the 1970s which affected significantly the nature and the local inhabitants as well. This study aimed to investigate the effect of this aridification process on dry and wet habitats of Illancs microregion. It reveals the ongoing processes in the landscape, referring to the previously affecting factors. In case of dry habitats, fragmentation and invasive species play important role as threatening factors. Wet habitats are significantly decreasing, shift of the vegetation zones can be observed. The stands are degraded, their steppification is dominant and can be observed only in the deepest parts of the depressions.